REDESAIN WEBSITE SI-PUMA (SISTEM INFORMASI INDEKS KEPUASAN MASYARAKAT) PADA KABUPATEN BANYUASIN MENGGUNAKAN METODE DESIGN THINGKING - Deni Erlansyah; Untari (P3M Institut Teknologi Pagar Alam, 2023)
This research report discusses the redesign of the SI-PUMA (Community Satisfaction Index Information System) website in Banyuasin Regency using the design thinking method. SI-PUMA is a digital application launched by the Regent of Banyuasin to measure and improve the quality of public services. However, the website had several shortcomings, such as incomplete information, untidy appearance, and difficult navigation. The researcher addressed these issues by conducting system analysis and design using the design thinking method, which involved five stages: empathize, define, ideate, prototype, and test. Several tools were used in the process, including UML, Python, MySQL, and HTML. The outcome of the research was a more attractive, informative, and interactive prototype and website of the SI-PUMA website. This research is expected to benefit the government, society, and the writer by enhancing the user experience of the SI-PUMA website. Future researchers are suggested to further develop the system, such as making it mobile-based, and to conduct UI/UX analysis by distributing questionnaires to the public.